Strategic Exploitation of the Wittig Reaction: Facile Synthesis of Heteroaromatics and Multifunctional Olefins - Karanam, Praneeth; Reddy, Ganapuram Madhusudhan; Lin, Wenwei (Synlett, 2018)
In this account, our group’s efforts towards exploring new substrates as precursors for the Wittig reaction have been discussed. Several new strategies developed by our group for the generation of requisite ylides for the Wittig reaction are highlighted. The idea behind the development of some chemoselective and diversity-oriented strategies are discussed in detail in a progressive manner. These strategies encompass a wide range of substrates that are employed for the synthesis of an array of heterocycles and multifunctional olefins and present a huge scope for their application on an industrial level.1 Introduction2 Development of New Methods to Effect Intramolecular Wittig Reaction3 Development of a Catalytic Wittig Reaction4 New Synthesis of Bis-Heteroarenes5 Direct β-Acylation of 2-Arylidene-1,3-indandiones6 Doubly Chemoselective Protocol for the Diversity-Oriented Synthesis of Coumarin Derivatives7 Conclusion
Keywords: Wittig reaction; phosphine; heteroarene; ylide; chemoselectivity; diversity-oriented synthesis; phospha-Michael addition; acylation